Handbook of Research on Digital Media and Advertising
DOI: 10.4018/978-1-61692-020-3.ch007
|View full text |Cite
|
Sign up to set email alerts
|

Race-Specific Advertising on Commercial Websites

Abstract: Avatars and anthropomorphic characters by marketers are becoming more commonplace on commercial web sites. Moreover, a trend among marketers is to use ethnically ambiguous models in advertising to appeal to specific consumer segments. This study helps our understanding of not only how best to segment and appeal to racially diverse consumers but how people interact with virtual human agents in relationship to the literature on audience response to real humans. It was predicted that Blacks would respond more pos… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 38 publications
0
1
0
Order By: Relevance
“…Of the few studies investigating people’s perception of racial ambiguity, one found that racially ambiguous synthetic characters are as effective as racially matched ingroup characters in generating identification and positive consumer attitudes ( Appiah & Elias, 2011 ). Another found objectively measured positive responses from audiences toward racially ambiguous models relative to unambiguous ones ( Read, 2020 ).…”
Section: Race Racial Ambiguity and Projection Of An Individual’s Own ...mentioning
confidence: 99%
“…Of the few studies investigating people’s perception of racial ambiguity, one found that racially ambiguous synthetic characters are as effective as racially matched ingroup characters in generating identification and positive consumer attitudes ( Appiah & Elias, 2011 ). Another found objectively measured positive responses from audiences toward racially ambiguous models relative to unambiguous ones ( Read, 2020 ).…”
Section: Race Racial Ambiguity and Projection Of An Individual’s Own ...mentioning
confidence: 99%